2012
DOI: 10.1101/cshperspect.a012070
|View full text |Cite
|
Sign up to set email alerts
|

Opiate-Induced Molecular and Cellular Plasticity of Ventral Tegmental Area and Locus Coeruleus Catecholamine Neurons

Abstract: The study of neuronal adaptations induced by opiate drugs is particularly relevant today given their widespread prescription and nonprescription use. Although much is known about the acute actions of such drugs on the nervous system, a great deal of work remains to fully understand their chronic effects. Here, we focus on longer-lasting adaptations that occur in two catecholaminergic brain regions that mediate distinct behavioral actions of opiates: ventral tegmental area (VTA) dopaminergic neurons, important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 100 publications
1
68
0
Order By: Relevance
“…Mouse VTA Nts neurons may instead contain either glutamate or GABA and project locally within the VTA to directly regulate DA neuron firing (Omelchenko and Sesack, 2009). Intriguingly, the small number of TH-negative Nts neurons was primarily detected in the caudal VTA along the rostral lateral borders, where the majority of VTA GABA neurons reside (Mazei-Robison and Nestler, 2012). These data suggest that mouse VTA Nts neurons could be GA-BAergic, and might provide local inhibitory control over neighboring DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse VTA Nts neurons may instead contain either glutamate or GABA and project locally within the VTA to directly regulate DA neuron firing (Omelchenko and Sesack, 2009). Intriguingly, the small number of TH-negative Nts neurons was primarily detected in the caudal VTA along the rostral lateral borders, where the majority of VTA GABA neurons reside (Mazei-Robison and Nestler, 2012). These data suggest that mouse VTA Nts neurons could be GA-BAergic, and might provide local inhibitory control over neighboring DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Second, given the suppression of LC firing produced by autocrine release of galanin discussed earlier, one might predict that NE depletion would phenocopy increased galanin transmission; indeed, this is the case in many instances. For example, like transgenic galanin overexpression or galanin receptor agonist administration, selective suppression of NE transmission via knockout of α1-adrenergic receptors or the NE biosynthetic enzyme dopamine ÎČ-hydroxylase, 6-OHDA lesions, or the administration of adrenergic receptor antagonists can attenuate the rewarding effects of morphine and withdrawal symptoms (Drouin et al, 2002; Maldonado, 1997; Mazei-Robison and Nestler, 2012; Olson et al, 2006; Sahraei et al, 2004; Ventura et al, 2005; Weinshenker and Schroeder, 2007; Zarrindast et al, 2002). Similar to manipulations of galanin itself, suppression of NE transmission has no effect for the most part on operant psychostimulant self-administration, but we and others have shown that psychostimulant conditioned place preference and reinstatement are also reduced upon blockade of NE signaling (Leri et al, 2002; Mantsch et al, 2010; Schroeder et al, 2010; Schroeder et al, 2013; Smith and Aston-Jones, 2011; Ventura et al, 2007; Vranjkovic et al, 2014; Wee et al, 2008; Weinshenker and Schroeder, 2007; Zhang and Kosten, 2005; Zhang and Kosten, 2007) (our unpublished data).…”
Section: Addictionmentioning
confidence: 99%
“…Many studies focus on chronic drug administration (Harris and Aston-Jones, 1994; Hemby et al, 1995; Kaufling and Aston-Jones, 2015;Mazei-Robison and Nestler, 2012); however, it is unknown how drug exposure paired with withdrawal alters catecholamine signaling in regions associated with the addiction cycle. Since appetitive and aversive stimuli elicit opposing responses from catecholamines (Park et al, 2012;Roitman et al, 2008;Twining et al, 2015), we hypothesized dopamine and norepinephrine signal reciprocally during drug exposure and withdrawal.…”
Section: Introductionmentioning
confidence: 99%